Barnacle inspired high-strength hydrogel for adhesive - Hao, Dezhao; Li, Xingchao; Yang, Enfeng; Tian, Ye; Jiang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Barnacle exhibits high adhesion strength underwater for its glue with coupled adhesion mechanisms, including hydrogen bonding, electrostatic force, and hydrophobic interaction. Inspired by such adhesion mechanism, we designed and constructed a hydrophobic phase separation hydrogel induced by the electrostatic and hydrogen bond interaction assembly of PEI and PMAA. By coupling the effect of hydrogen bond, electrostatic force and hydrophobic interaction, our gel materials show an ultrahigh mechanical strength, which is up to 2.66 ± 0.18 MPa. Also, benefit from the coupled adhesion forces, as well as the ability to destroy the interface water layer, the adhesion strength on the polar materials can be up to 1.99 ± 0.11 MPa underwater, while that of the adhesion strength is about 2.70 ± 0.21 MPa under silicon oil. This work provides a deeper understanding of the underwater adhesion principle of barnacle glue. Furthermore, our bioinspired strategy would provide an inspiration for the fabrication of high mechanical gel materials, and the rapid strong adhesive used in both water and organic solvents.